Evolution of short-range order and its effects on the plastic deformation behavior of single crystals of the equiatomic Cr-Co-Ni medium-entropy alloy. (15th January 2023) - Li, Le; Chen, Zhenghao; Kuroiwa, Shogo; Ito, Mitsuhiro; Yuge, Koretaka; Kishida, Kyosuke; Tanimoto, Hisanori; Yu, Yue; Inui, Haruyuki; George, Easo P.
Abstract: Short-range ordering (SRO), its evolution in the equiatomic Cr-Co-Ni medium-entropy alloy (MEA), and its effects on mechanical properties were investigated by, respectively, electrical resistivity measurements and tension and compression tests on single crystal specimens at room temperature and liquid nitrogen temperature. SRO below 973 K can be monitored by changes in electrical resistivity, which increases gradually with time to a saturation value during isothermal annealing in the temperature range of 673–973 K. While the time required to reach saturation is shorter at higher temperatures, the saturation resistivity is higher at lower temperatures, indicating a higher degree of SRO at lower temperature although it takes longer to reach saturation because of slower kinetics. No significant change in the plastic deformation behavior is found at room temperature and 77 K for different degrees of SRO. The yield stress as well as the slip localization behavior are basically the same after SRO, and the magnitude of yield drop does not correlate with the degree of SRO. Tensile stress-strain curves are not much affected by SRO up to high strain levels, resulting in identical shear stresses for the onset of deformation twinning at room temperature regardless of the degree of SRO. The dislocation structure, variations in dislocation dissociation width, and stacking fault energy are all essentially unchanged. Graphical abstract: Image, graphical abstract